PENGARUH KINERJA KEUANGAN DAN MAKROEKONOMI TERHADAP RETURN SAHAM PADA SUBSEKTOR MAKANAN DAN MINUMAN PERIODE 2011-2015 - Edhi Asmirantho; Yudhia Mulya; Dinar Ardian Firmansyah (Universitas Pakuan, 2016)
Abstract This study is aimed to test the effect of financial performance and macroeconomics variables in explaining stock returns. The study conducts two regression models. The first model included only financial performance as independent variables which consist of current ratio, debt to equity ratio, earnings per share, return on assets, economic value added, inventory turnover, and price to earnings ratio. Then the first model is extended to the second model by adding macroeconomics variables which consist of interest rate and inflation. Pooled least squares regression is applied in this study and all of the assumptions to obtain best linier unbiassed estimator are met. The extended model results in an increase of adjusted R-squared value from 46,9% to 60,84%. Keywords: Financial Performance, Interest Rate, Inflation, Stock Return